Creating a digital memory notebook application for individuals with mild cognitive impairment to support everyday functioning. (18th May 2020) - Raghunath, Nisha; Dahmen, Jessamyn; Brown, Katelyn; Cook, Diane; Schmitter-Edgecombe, Maureen
Abstract: Purpose: Memory impairment can necessitate use of external memory aids to preserve functional independence. As external aids can be difficult to learn and remember to use, technology may improve the efficacy of current rehabilitation strategies. We detail the iterative development of a digital application of a paper-and-pencil memory notebook. Methods: Twenty participants (aged 54+) of varying levels of cognitive ability were recruited for four iterations of usability testing (five participants per iteration). Each participant completed a series of tasks using the digital memory notebook (DMN), followed by questionnaires that assessed satisfaction (Questionnaire for User Interface Satisfaction) and usability ratings (Post-Study System Usability Questionnaire) for the application. Results and Conclusions: Between Iterations 2 and 5, participants demonstrated marked reductions in time to complete several types of tasks (e.g., add event, navigate interface) using the DMN. Participants in Iteration 5 also rated all subscales of both the usability and satisfaction questionnaires very highly. Faster task completion times were correlated with more favourable system ratings. However, neither task performance times nor system ratings were correlated with cognitive abilities, scheduling tool use or comfort with technology. Both the questionnaire and performance-based data indicate the final iteration of the DMN was easy to use. Furthermore, the application was user-friendly despite individual differences in cognitive ability, familiarity with scheduling tools and comfort with technology. Future work will demonstrate whether the DMN will support everyday retrospective and prospective memory lapses and increase the functional independence and quality of life for persons with cognitive impairment. Implications for rehabilitation: Building on practice standards and user-centred design, the digital memory notebook (DMN) application is an "all-in-one" memory aid and organizational tool with an intuitive interface designed to help improve everyday functioning. The DMN's today page, to do list and calendar functions can support everyday prospective and retrospective memory abilities. The DMN's notes, journaling and motivational functions can support longer-term goal planning and mood management. The DMN's alarm functions can support learning to use the DMN and serve as reminders to support prospective memory and aid in activity completion.